1991
DOI: 10.1080/09553009114552511
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Step-down Heating on the Interaction between Heat and Radiation in a C3H Mammary Carcinomain Vivo

Abstract: The effect of step-down heating (SDH) on the interaction between heat and radiation was investigated in a C3H mammary carcinoma in vivo. SDH consisted of an initial sensitizing treatment (ST) performed at 44.5 degrees C or 43.5 degrees C followed by a lower temperature test treatment (TT) in the range 41.0-43.0 degrees C. Step-up heating (SUH), i.e. TT followed by ST, and single heating were used as controls. The end-point was the radiation dose needed to control 50% of the tumours (TCD50). The results were ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The r value for the ST temperatures used was 0.45 Overgaard 1987, 1990). Thus, the degree of SDH-induced radiosensitization was only dependent on the extent of the priming ST heat damage and not on the specific ST heating times or temperatures used (Lindegaard et al 1991a). Thus, the degree of SDH-induced radiosensitization was only dependent on the extent of the priming ST heat damage and not on the specific ST heating times or temperatures used (Lindegaard et al 1991a).…”
Section: J C Lindegaardmentioning
confidence: 94%
See 3 more Smart Citations
“…The r value for the ST temperatures used was 0.45 Overgaard 1987, 1990). Thus, the degree of SDH-induced radiosensitization was only dependent on the extent of the priming ST heat damage and not on the specific ST heating times or temperatures used (Lindegaard et al 1991a). Thus, the degree of SDH-induced radiosensitization was only dependent on the extent of the priming ST heat damage and not on the specific ST heating times or temperatures used (Lindegaard et al 1991a).…”
Section: J C Lindegaardmentioning
confidence: 94%
“…Lindegaard et al (1991a) showed that both an increase in heating time and in temperature of the TT enlarged the radiosensitizing effect of SDH (Figure 7). Lindegaard et al (1991a) showed that both an increase in heating time and in temperature of the TT enlarged the radiosensitizing effect of SDH (Figure 7).…”
Section: Effect Of Sdh On Hyperthermic Radiosensitization In Vitro Anmentioning
confidence: 97%
See 2 more Smart Citations
“…This occurred most strongly with a stepdown protocol (SRF 3.5). Enhanced thermoradiosensitization by preirradiation step-down heating has been observed in rodent cells [32] and in animal tumor systems with LDRI at 37°C [33] and HDRI at 4143°C [34]. In the animal studies maximal thermoradiosensitization was achieved when heat was given simultaneously with radiation.…”
Section: Discussionmentioning
confidence: 95%